The Effectiveness of E-Module Use on the Science Learning Outcomes of Sixth-Grade Primary School Students - Novra Arina; Mustaji; Citra Fitri Kholidya; Vivi Rulviana; Muhammad Rapii; Nur Arifinza Desi Wardana (Postgraduate, University of Mataram, 2025)
This study aimed to examine the effectiveness of an IPAS e-module in improving science learning outcomes of Grade VI students at State Primary School 04 Kota Solok. A quasi-experimental non-equivalent control group pretest–posttest design was used, involving an experimental class that learned with the e-module and a control class that received conventional instruction. Data were collected using pretest and posttest scores and analyzed through prerequisite tests (normality, homogeneity, and initial equivalence), independent-samples t-test, and normalized gain (N-gain). The results showed that the posttest scores of the experimental group were significantly higher than those of the control group (p < 0.05). The experimental class achieved an N-gain of 0.68, categorized as moderate and close to the upper limit of the medium range, while the control class obtained an N-gain of 0.29, classified as low. These findings indicate that the e-module substantially improves students’ science learning outcomes and supports more effective technology-enhanced IPAS learning in primary schools.